Original paperScars after self-harm - Iljin, Aleksandra; Kruk-Jeromin, Julia (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2010)
Introduction : Self-inflicted scars are often located on exposed body sites and may accompany some syndromes and substance abuse. Treatment of these scars depends on location, size, cause, and time since their formation, including physical, pharmacological and surgical methods and psychotherapy applied as combination or monotherapy. Material and methods : There were 18 patients (8 females, 10 males) who underwent surgical treatment for self-inflicted scars at the Department of Plastic, Reconstructive and Aesthetic Surgery, Medical University of Lodz in the years 1999-2008. In the publication we review data on causes and pathomorphology of these lesions in the aspect of surgical treatment. Results : Early and late postoperative results in patients of the study group were good. Conclusions : Combining surgical, physical, pharmacological and psychiatric treatment gave optimal therapeutic results in patients with self-inflicted scars. A variety of corrective methods for self-inflicted scars gives them an acceptable appearance but without total elimination.